Understanding the two-way interactions between aardvark (Orycteropus afer) burrowing and the surrounding landscape characteristics at Rietvlei Nature Reserve, South Africa - Haussmann, Natalie (University of Pretoria, 2022)
Dissertation (MSc (Geography))--University of Pretoria, 2021.